Diagnostic Dilemma in Appendiceal Mucormycosis: A Rare Case Report - Sali Priyanka Akhilesh; Yadav Kamal Sunder; Pande Prasad; George Mary Asha; Agarwal Mohan; Mehta Hitesh (Case Reports in Surgery)
Appendiceal mucormycosis is a rare life-threatening infection seen in immunocompromised patients. It is usually seen in chemotherapy induced neutropenia in patients with hematological malignancies. Clinically, the symptoms and signs may be masked due to ongoing corticosteroids. The condition may mimic bacterial appendicitis and the less serious condition, typhlitis. The disease demands prompt surgical debulking and aggressive antifungal treatment. However, surgery is delayed due to the poor performance status and severe neutropenia. This may lead to perforative peritonitis and further dissemination. The survival rates of such disease are dismal. Unfortunately, the diagnosis may be confirmed only on histological examination of the surgically excised tissue. Very few cases have been reported so far. We present here once such a fatal case of appendiceal mucormycosis in a 14-year-old boy who was immunosuppressed due to intensive induction therapy for Acute Myeloblastic Leukemia.